[Amelia Earhart with Cal Poly Aeronautics Department, 1936] (1936)
Amelia Earhart and Cal Poly Aeronautics Department faculty and students standing in front of the Aeronautics building when she visited the school on Thursday, June 25, 1936. Standing left to right: Aero instructor M. C. Martinsen (Class of 1917); Earhart colleague and Hollywood pilot Paul Mantz; student Philip Jensen; Earhart; and student Harley Smith. The aeronautics building was located in the approximate location of the Frank E. Pilling Building. Duplicate photo: ua-pho_00001069